Improvement of millet, sorghum, cowpeas and maize in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The research department of the Sahel Institute in Bamako, Mali has just released the results of trials conducted between 1981-1984 to compare different varieties of millet, sorghum, cowpeas and maize. They are the outcome of a regional crop...